Design, Synthesis, Characterization and Comparative Cytotoxic Evaluation of bis-(2- mercaptoacetate) gold (III) chloride - A. AlOmari, Nohad (Iraqi Journal of Pharmaceutical Sciences, 2017)
In recent years , the interest in gold (III) species have gained more and more attention for cancer chemotherapy , this was stimulating by the possibility to develop new agents with mode of action and clinical profile different from the established platinum metalodrugs. With this frame, recently new square planar Au(III) complexes (Au(L)(L’)n); where L=SCH2COO- ; L’=HSCH2COO- had been synthesized with S/O â€“ donor ligands. In this article and by the aim to replace, one of (L’) ligand by anion chloride ligand (which supposedly more relevant for the biodistribution of the compound than for its pharmacodynamic effects), new complex (Au(L’)2 Cl) was synthesized : (H (AuCl4) + 2 HSCH2COO -Na+ Au(L’)2 Cl) The prepared complex was characterized by elemental analysis, FTIR, H’NMR, UV, molar conductance and magnetic susceptibility and its anticancer activity was tested against Hep-2 cell line. The comparative figure of the cytotoxic activities of all the synthesized complexes against Hep-2 cell line , showed cytotoxic profile variant to the well- known anticancer drug cisplatin , indicated that there is no direct correlation exists between the nature of the ligands (L),(L’) and (Cl-) , their different arrangements around central metal core with their collectives cytotoxic results. Key words: S/O â€“ donor ligands. , gold (III), cytotoxic